Legal Consquences of A Contract Made by The Parties Thereout Arbiral Award - Fizara Nugra Anisa (Budapest International Research and Critics University, 2019)
As a top-10 gold mining countries, Indonesia becomes the most attractive investors destination in mining sector. Those foreign investors shall be a Joint Venture Company with a domestic company. That joint venture company later must be making an agreement with Indonesia’s government in form contract of work. Conflict of interests are often happen within holding companies with joint venture company’s measure performing contract of work. In this case discussed in this writing, the holding companies are making an agreement of which the object of that agreement turns out being an object which is must be executed based on the case verdict between the joint venture company and the government of Indonesia. The losingparty may apply for agreement revocation or derdenverzet over the verdict.